Is Son Preference Disappearing from Bangladesh? - Niaz Asadullah; Nazia Mansoor; Teresa Randazzo; Zaki Wahhaj (Institute of Labor Economics (IZA), 2020)
Historically, son preference has been widely prevalent in South Asia, manifested in the form of skewed sex ratios, gender differentials in child mortality, and worse educational investments in daughters versus sons. In the present study, we show, using data from a purposefully designed nationally representative survey for Bangladesh, that among women of childbearing age, son bias in stated fertility preferences has weakened and there is an emerging preference for gender balance. We examine a number of different hypotheses for the decline in son preference, including the increasing availability of female employment in the manufacturing sector, increased female education, and the decline of joint family living. Using survival analysis, we show that in contrast to stated fertility preferences, actual fertility decisions are still shaped by son preference.
Keywords: J11; J13; J16; O12; 330; fertility; gender bias; birth spacing; female employment; Bangladesh